Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Rashmi Das; Abhishek Ankur Balmik; Subashchandrabose Chinnathambi (Journal of Neuroinflammation, 2020)
Abstract Background Alzheimer’s disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-β plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40WT oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-β sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40WT oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11+ Iba1high microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer’s disease condition.